(untitled) (Journal of Laboratory Animal Science, 2024)
Eight-week-old male and female BALB/c mice that were procured and kept for quarantine experienced 10% mortality in males and 3.3% in females from the second day onwards with partially mutilated carcasses in both cages. Considering the stress due to travel Vitamin C was provided in the drinking water from day 4. The percentage of mortality was reduced as compared to the first day however mortality continued to 5th day. Furthermore, the application of eucalyptus oil in the cage and animal body surface of the animals for one week repeatedly results in a substantial decrease in % mortality in male and female mice.